2021
DOI: 10.1038/s41438-021-00671-3
|View full text |Cite
|
Sign up to set email alerts
|

Defense responses of arbuscular mycorrhizal fungus-colonized poplar seedlings against gypsy moth larvae: a multiomics study

Abstract: Arbuscular mycorrhizal (AM) fungi may help protect plants against herbivores; however, their use for the pest control of woody plants requires further study. Here, we investigated the effect of Glomus mosseae colonization on the interactions between gypsy moth larvae and Populus alba × P. berolinensis seedlings and deciphered the regulatory mechanisms underlying the mycorrhizal-induced resistance in the leaves of mycorrhizal poplar using RNA-seq and nontargeted metabolomics. The resistance assay showed that AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 51 publications
7
23
0
Order By: Relevance
“…It has been commonly reported in both laboratory and field experiments that plant inoculation with AMF promote growth and increase biomass, a phenomenon considered as the positive mycorrhizal growth response (MGR) ( Bernaola et al, 2018 ; Zhang et al, 2019 ). Positive MGR was previously found to be due to the improved uptake and transfer of nutrients (usually phosphorus and nitrogen) ( Jiang et al, 2021 ), which is consistent with the findings of this study. E. nutans inoculated with F. mosseae significantly increased plant biomass compared to the non-inoculated treatment, in addition to increasing the uptake of nitrogen and phosphorus.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It has been commonly reported in both laboratory and field experiments that plant inoculation with AMF promote growth and increase biomass, a phenomenon considered as the positive mycorrhizal growth response (MGR) ( Bernaola et al, 2018 ; Zhang et al, 2019 ). Positive MGR was previously found to be due to the improved uptake and transfer of nutrients (usually phosphorus and nitrogen) ( Jiang et al, 2021 ), which is consistent with the findings of this study. E. nutans inoculated with F. mosseae significantly increased plant biomass compared to the non-inoculated treatment, in addition to increasing the uptake of nitrogen and phosphorus.…”
Section: Discussionsupporting
confidence: 93%
“…Mycorrhizal symbiosis as a potential pest control strategy may be an effective alternative to some chemical pesticides in contemporary agriculture ( Jiang et al, 2021 ). However, the applicability of this insect resistance mechanism in alpine forage plants is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flavonoids and secondary metabolites have a strong impact on defense against pathogens because of their antimicrobial activity, but they also reduce plant quality to insects, thus reducing the range of hosts (Burghardt et al, 2001). Previous studies confirmed that oxylipins and JA-related responses are tightly regulated in mycorrhized plants (Sanchez-Bel et al, 2018;Jiang et al, 2021;Rivero et al, 2021). LOX and AOS upregulation in myco rrhized poplar is correlated with an increase in 4-coumarate-CoA ligase, chalcone isomerase, and other flavonoid-related genes.…”
Section: Discussionmentioning
confidence: 96%